Cultivation and lipid extraction of scenedesmus sp. from unimas lake and scenedesmus dimorphus from texas - Wan Arina Azrinor, binti Yamin (Universiti Malaysia Sarawak (UNIMAS), 2014)
The search for a more sustainable and renewable biofuels feed sources has drastically increased. One of the sources that have received much attention is microalgae as cultivation of this organism does not require much land and is less expensive. Their cultivation can also be carried out under natural condition such as tanks or open pond production systems. The current research aims to conduct a study on the mass production and lipid yield of green microalgae, Scenedesmus sp. which was previously isolated from a lake in UNIMAS East Campus and Scenedesmus dimorphus which was purchased from the University of Texas. The microalgae were cultured indoors in 2 L and 9 L carboys in Modified Bristol’s Medium (MBM) and then were cultured outdoors in 3 tanks which volume was about 351.523 L. All of the cultured were enriched with chicken manure with concentration of 3.5%. The dry weight of Scenedesmus sp. and Scenedesmus dimorphus obtained from outdoor cultivation were 20.88 g and 36.98 g respectively. The lipid yield produced by Scenedesmus sp. of UNIMAS Lake was 38.17% of the dry weight. The lipid yield by Scenedesmus dimorphus could not be obtained.